Alternative Assessment Tools for the Writing Skill Development of EFL Learners - Cuesta, Paola Vanessa Navarrete; Mayorga, Jazmina Ivonne Mena; Padilla, Yajaira Natali Padilla; Mayorga, Angel Paul Obregon (European Scientific Journal, ESJ, 2019)
This paper focuses on improving the writing skill through the application of strategies based on alternative assessment to EFL students in a private university of Ecuador. This inquiry analyses how the application of alternative assessment tools affect the development of the writing skill of EFL learners. The target population of this study was 23 students who take English lessons at the first level. This research used the quasi-experimental design with an experimental group only. The instruments used to collect data were a pretest and a posttest applied to the experimental group. The results obtained in both tests were compared and analyzed using the percentage system represented in charts. After the data analysis, it was concluded that alternative assessment positively affects the development of the writing skill of EFL learners. Thus, they have all enhanced their writing competence. Therefore, this study concludes that after the application of alternative assessment tools, students discovered that the writing process became more meaningful. Based on the findings, the researchers recommend the use of different alternative assessment tools in order to enrich the writing skill.